Questioning Subalternity: Between Colonizer and Colonized in Gayatri Chakravorty Spivak’s “Can the Subaltern Speak?” - Monika Sharma; Poonam Rani (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
In India the practice of sati was very common and many women who became part of the rituals did it out of their love for their husbands. The society has played a major role in making sati a common phenomenon in the country so as to deny separate existence from men. The essay vindicates the apprehension of women in India who practice the widow sacrifice known as ‘Sati’ The practice of sati in the pre independent India was considered as a part of a barbaric culture by the Western world. Gyatri Chakrovorty Spivak has become an authoritative voice of the post-colonial period and through her cultural and critical theories tried to challenge the legacy of colonialism. India is a land of varieties and vitalities that is divided into different states in the name of class, religion, language, authenticity, gender and citizenship. In this scattered outlook the condition of the subaltern is all the most pathetic. She came to the forefront of the literary circle with her celebrated essay “Can the Subaltern Speak”. Her critical discourse raises the issues of marginal subjects such as the place of the subaltern women in the society and their empowerment.